Bring your own camera to the trap: An inexpensive, versatile, and portable triggering system tested on wild hummingbirds - Rico‐Guevara, Alejandro; Mickley, James (Ecology and evolution, 2017)
The study of animals in the wild offers opportunities to collect relevant information on their natural behavior and abilities to perform ecologically relevant tasks. However, it also poses challenges such as accounting for observer effects, human sensory limitations, and the time intensiveness of this type of research. To meet these challenges, field biologists have deployed camera traps to remotely record animal behavior in the wild. Despite their ubiquity in research, many commercial camera traps have limitations, and the species and behavior of interest may present unique challenges. For example, no camera traps support high‐speed video recording. We present a new and inexpensive camera trap system that increases versatility by separating the camera from the triggering mechanism. Our system design can pair with virtually any camera and allows for independent positioning of a variety of sensors, all while being low‐cost, lightweight, weatherproof, and energy efficient. By using our specialized trigger and customized sensor configurations, many limitations of commercial camera traps can be overcome. We use this system to study hummingbird feeding behavior using high‐speed video cameras to capture fast movements and multiple sensors placed away from the camera to detect small body sizes. While designed for hummingbirds, our application can be extended to any system where specialized camera or sensor features are required, or commercial camera traps are cost‐prohibitive, allowing camera trap use in more research avenues and by more researchers. The features of available camera traps can often limit the study of animal behavior in the wild. We present a triggering system that can be paired with specialized cameras and sensors to relax these restrictions, while being cheap and easy to build. Our application used specialized high‐speed video cameras to film feeding behavior of wild hummingbirds, demonstrating the usefulness of our approach with a challenging subject.